2022
DOI: 10.1186/s12864-022-08407-w
|View full text |Cite
|
Sign up to set email alerts
|

Proteome and Transcriptome Analysis of Gonads Reveals Intersex in Gigantidas haimaensis

Abstract: Sex has proven to be one of the most intriguing areas of research across evolution, development, and ecology. Intersex or sex change occurs frequently in molluscs. The deep-sea mussel Gigantidas haimaensis often dominates within Haima cold seep ecosystems, but details of their reproduction remain unknown. Herein, we conducted a combined proteomic and transcriptomic analysis of G. haimaensis gonads to provide a systematic understanding of sexual development in deep-sea bivalves. A total of 2,452 out of 42,238 g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Considering the anatomical observations only, another possibility could have been that the intersex individuals were undergoing sex change (sequential hermaphroditism). For instance, in a recent study of Gigantidas haimaensis mussels from cold seep ecosystems in the South China Sea, Shi et al . (2022) found that male gonads contained oocytes (while female gonads did not contain spermatocytes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the anatomical observations only, another possibility could have been that the intersex individuals were undergoing sex change (sequential hermaphroditism). For instance, in a recent study of Gigantidas haimaensis mussels from cold seep ecosystems in the South China Sea, Shi et al . (2022) found that male gonads contained oocytes (while female gonads did not contain spermatocytes).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 13, 2023. ; https://doi.org/10.1101/2023.04.11.536409 doi: bioRxiv preprint destroy most of the vent communities in a given region (see the recent eruption of the submarine volcano Hunga Tonga -Hunga Ha'apai in December 2021, Gupta et al, 2022). In a recent study of Gigantidas haimaensis mussels from cold seep ecosystems in the South China Sea, Shi et al (2022) found that male gonads contained oocytes (while female gonads did not contain spermatocytes).…”
Section: A Unique Pair Of Xy Chromosomes Across the Three Species?mentioning
confidence: 99%
“…Considering the anatomical observations only, another possibility could have been that the intersex individuals were undergoing sex change (sequential hermaphroditism). For instance, in a recent study of Gigantidas haimaensis mussels from cold seep ecosystems in the South China Sea, Shi et al (2022) found that male gonads contained oocytes (while female gonads did not contain spermatocytes). Combining proteomic and transcriptomic analyses with their histological observations, the authors hypothesized that these males were intersex individuals undergoing sex change, a strategy observed in other Bathymodiolinae (Laming et al, 2018) possibly favoured by the ephemeral and patchy distribution of deep sea vent and cold seep habitats.…”
Section: What Is the Sexual System Of Alviniconcha Kojimai And How Is...mentioning
confidence: 99%
“…These findings suggest the potential utility of these proteins as biomarkers for the evaluation of deep-sea mining endeavors in the future (Kwan et al, 2019). Therefore, proteomics research has been conducted on various marine organisms, including barnacle (Yan et al, 2020), deep-sea mussel (Ponnudurai et al, 2020;Shi et al, 2022), deep sea copepods (Renz et al, 2021), deep sea isopods (Paulus et al, 2022), and so on.…”
Section: Introductionmentioning
confidence: 99%